A universal surface enhanced Raman spectroscopy (SERS)-active graphene cathode for lithium–air batteries. Issue 104 (27th October 2016) - Liu, Kewei; Yu, Zitian; Zhu, Xiaowen; Zhang, Shuo; Zou, Feng; Zhu, Yu
Abstract : A uniform SERS-active graphene electrode was used in lithium–oxygen batteries. Abstract : Nonaqueous lithium–air (Li–O2 ) batteries, with their high theoretical energy densities far exceeding those of conventional Li-ion batteries, have attracted significant research interest over the past decade. However, the practical realization of Li–O2 batteries is still confronted with the challenge of electrode side reactions that lead to severe solvent/electrode degradation upon cycling. To understand the reaction process on the electrode, it is necessary to obtain detailed information about the chemicals formed on the Li–O2 battery electrode. Herein, a universal method to fabricate large-area regularly patterned gold nano-dots using an anodic aluminum oxide (AAO) mask was developed. The gold nano-dots were patterned on to conductive substrates such as Au film and graphene, and then the films were used as SERS (Surface Enhanced Raman Spectroscopy)-active cathodes in Li–O2 batteries. The discharge products on the different electrodes (graphene and gold) were analyzed and the results indicated that the SERS electrode will be a useful tool for studying the reaction process on lithium–air cathodes.